Politeness Strategies in WhatsApp Cancellation Messages: A Socio-Pragmatic Analysis in the Central Java Tourism Industry - Budi Purnomo; Nunun Tri Widarwati (Journal of Pragmatics Research, 2025)
This study investigates the politeness strategies employed by Indonesian hotel and travel agent reservation staff in responding to reservation cancellations communicated via WhatsApp by prospective guests and tourists. Focusing on service providers’ responses, the study explores how politeness is pragmatically constructed in informal digital interactions within the Central Java tourism industry. Drawing on Brown and Levinson’s politeness theory, the research employs a qualitative descriptive method. Data were collected from authentic WhatsApp conversations between service staff and Indonesian clients, particularly concerning cancellation messages initiated by the clients. The analysis reveals the dominant use of both negative and positive politeness strategies, including indirect expressions, apologies, expressions of gratitude, empathy, and hedging. These strategies reflect culturally grounded efforts to maintain social harmony, express professionalism, and mitigate face-threatening acts. Linguistic features such as mohon maaf sebelumnya (“we apologize in advance”) and personalized honorifics like Pak, Bu, Mas, and Mbak, alongside informal tones, illustrate the hybrid nature of politeness in digital service discourse in Central Java. The study demonstrates that politeness functions as both a linguistic and strategic tool for managing client relationships and that it embodies the high-context communicative norms of Javanese culture. These findings contribute to a socio-pragmatic understanding of politeness in mediated tourism communication and offer practical insights for improving client engagement in digital service encounters.